Increasing Achievement In Learning Al-Qur'an Hadist Through Implementing The Tahfidzul Qur'an Program In High School - Larasati, Rachmalia Dewi; Latifatul Inayati, Nurul (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research examines the impact of the implementation of the Tahfidzul Qur'an program on the improvement of students' learning achievements in Al-Qur'an Hadith at SMA Muhammadiyah 1 Karanganyar. The study uses a qualitative research approach with a descriptive phenomenological design, employing interviews, observations, and documentation as data collection methods. The data were analyzed using a triangulation technique to ensure accuracy and validity. The findings indicate that the Tahfidzul Qur'an program has a significant positive effect on students' academic performance in Al-Qur'an Hadith. The program, which incorporates methods such as Talqin, Talaqqi, Takrir, and Muroja'ah, enhances students' ability to memorize and understand the Qur'an, which in turn supports their learning in related subjects like Al-Qur'an Hadith. Furthermore, the structured environment provided by the program, supported by regular evaluations and parent involvement, motivates students to engage more deeply with the material, resulting in improved cognitive skills, discipline, and time management.The study also identifies key factors that contribute to the program’s success, including regular evaluations, strong collaboration between the school and parents, and an integrated curriculum. However, challenges such as the limited number of qualified Tahfidz teachers and the students' busy schedules were also noted. These findings suggest that while the program has a substantial positive impact, there is a need for further improvements, particularly in terms of teacher capacity and time management for students. This research contributes to the understanding of how religious education programs, specifically the Tahfidzul Qur'an, can significantly influence academic performance in related subjects. The findings provide insights for educators and policymakers on integrating memorization programs effectively into academic curricula, especially in Islamic educational settings. The study highlights the importance of a holistic approach to learning that combines spiritual, cognitive, and academic development, and it offers recommendations for optimizing such programs to maximize their benefits for students.